2013
DOI: 10.1155/2013/131757
|View full text |Cite
|
Sign up to set email alerts
|

Dorsally Comminuted Fractures of the Distal End of the Radius: Osteosynthesis with Volar Fixed Angle Locking Plates

Abstract: Background. Dorsally comminuted distal radius fractures are unstable fractures and represent a treatment challenge. The objective of this study was to evaluate the functional and radiological outcome of dorsally comminuted fractures of the distal radius fixed with a volar locking plate. Patients and Methods. Thirty-three consecutive patients with dorsally comminuted fractures of the distal end of the radius were treated by open reduction and internal fixation with AO 2.4 mm (n = 19)/3.5 mm (n = 14) volar locki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 20 publications
(38 reference statements)
2
17
0
Order By: Relevance
“…As with all articular fractures, mobilization of the wrist also facilitates good joint lubrication and prevents stiffness [16] . Our results in terms of regaining the range of motion and radiological parameters correlates well with other studies [9,11,18] . Tendon related complications in our study are much less (3.8%) compared to the previous studies.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As with all articular fractures, mobilization of the wrist also facilitates good joint lubrication and prevents stiffness [16] . Our results in terms of regaining the range of motion and radiological parameters correlates well with other studies [9,11,18] . Tendon related complications in our study are much less (3.8%) compared to the previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…There is a layer of pronator quadratus muscle which inhibits direct contact of the tendons with the plate, 3. The volar surface is more flatter making plate application easier [11,12] . The screws lock with the plate holes, which provide angular stability, prevents backout of screws and plate, and thus minimizes the chances of secondary displacement following fracture reduction and fixation [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…Locking plates offer an attractive alternative for management of these fractures due to possibility of a more stable construct on account of angular stability of locking screws. Additional possible advantages of these plates include, decreased soft tissue complications and absence of secondary displacement of fracture fragments even in the absence of adequate contouring of plates [14][15][16]. The present study was therefore conducted in a prospective manner to evaluate the role of locking compression plates in distal end radius fractures.…”
Section: Discussionmentioning
confidence: 99%
“…The results are comparable with other studies. 11 showed that ulnar variance became equal to unaffected side in 77.8%(n=21)patients while 0.4mm in 22.2%(n=6)patients, radial inclination was similar to unaffected side(20-25degree) in 48.2 %( n=13)while 51.8%(n=14) showed 26.8degree,radial height similar to unaffected side(10-13mm) in 40.7%(n=11) patients Paritosh Gogna et al (2013) [13] showed palmar angulation5.86° ± 6.74°, Radial inclination 23. [14] the average palmar angulation was 6.7° (range, 2° of dorsal tilt to 15° of volar tilt), radial inclination averaged 20.2° (range, 20-25°), radial shortening averaged 0.7 mm (range, 0-2 mm) i.e radial height within 10-13mm.…”
Section: Mode Of Injurymentioning
confidence: 92%
“…R.E. Anakwe et al, (2010) [12] reported no complication and Paritosh Gogna et al (2013) [13] reported 9.9% loss of reduction, there was no hardware related complication or nonunion. Margaret W.M.…”
Section: Fracture Union Timementioning
confidence: 99%